A Transition Metal Catalyzed Reaction of Aromatic Acyl Chlorides with Epoxides - Achim Roloff (CHIMIA)
In a transition metal catalyzed reaction of aroyl chlorides with epoxides a change from palladium to ruthenium brings about a change in regioselectivity. A participation of the transition metal in the ring opening step is now evident.